PENINGKATAN KOMPETENSI PEDAGOGIK GURU MELALUI SUPERVISI AKADEMIK DENGAN PENDEKATAN KOLABORATIF DI SMP NEGERI 2 MODO KABUPATEN LAMONGAN - Hadi Hadi (Universitas Islam Lamongan, 2018)
Abstract: This study is about improving teachers' pedagogical competence through academic supervision with a collaborative approach in SMPN 2 Modo Lamongan. The problem of this study is whether through academic supervision with a collaborative approach it can improve pedagogical competence (ability and motivation) of teachers in SMPN 2 Modo Lamongan? The results of this study are if academic supervision uses a collaborative approach, the pedagogical competence of teachers in SMPN 2 Modo Lamongan will increase. The subjects of this study are six teachers of SMPN 2 Modo Lamongan. The researcher obtains data by using an instrument for evaluating teachers' performance, observations and field notes. In analyzing data the reasercher uses qualitative descriptive statistical data analysis techniques. From the results of data analysis in cycle I and cycle II, a conclusion can be drawn that through academic supervision with a collaborative approach, the pedagogical competence of teachers in SMPN 2 Modo, Lamongan has increased.Keywords: Teachers' pedagogical Competence, academic supervision, collaborative approach